TO VALUE THE EFFICIENCY OF PYRONARIDINE-ARTESUNATE AND ARTEMETHER-LUMEFANTRINE IN THE TREATMENT OF UNCOMPLICATED MALARIA OF PLASMODIUM SPP. IN BURKINA FASO. (12th February 2017) - Barry, Nouhoun; Kaboré, Naomie; Kabré, Zachari; Fofana, Aminata; Nikèma, Fréderic; Compaoré, Daniel; Somé, Fabrice; Zongo, Issaka; Djimdé, Abdoulaye; Ouédraogo, Jean
Abstract : Background: No safe and highly effective malaria vaccine is available today. The treatment drugs currently in use remain insufficient. Moreover, resistance to these drugs makes malaria control difficult. The development of new therapeutic drugs is required. This abstract is part of a survey from the WANECAM study entitled 'Randomised trial to assess the effect of repeated treatment of pyronaridine-artesunate (PA), dihydroartemisinin-piperaquine (DHA-PQ) and artemether-lumefantrine (AL) in patients presenting uncomplicated malaria in Bobo-Dioulasso, Burkina Faso'. We present here the analysis of the first episodes on the therapeutic efficiency of PA compared to AL, which is the first-line antimarial used in Burkina Faso. Methods: A total of 448 subjects were randomised to receive treatment (224 subjects in each arm). Malaria diagnosis was assessed by microscopy. Subjects were follow-up during 42 days. Treatment response was measured according to standard of care as per WHO guidelines of 2003. The correction of the cases of treatment failure by molecular biology techniques is under analysis. Results: On Day 28, the therapeutic failures were 3.35% in the PA group as against 18, 10% for the AL group. On Day 42, a significant increase of the treatment failures in every group is observed with a higher rate in the AL group (31.43%), against 17.22% in the PA group. Conclusions: This survey shows that less cases of treatment failure occurred in the patients' group treated with PA compared to the group treated with AL. These findings contributed to evidence base for a change in malaria treatment policy guidelines for uncomplicated malaria in Burkina Faso.